Designing an English Syllabus for Nursing Students based on need analysis in Indonesia - Dedi Bae (Universitas Negeri Makassar, 2017)
This paper aims to find out (1) Learning needs of the students, (2) Language needs of the students, and (3) Design an appropriate English syllabus based on the students’ need. The researcher applied descriptive quantitative method. This research used some techniques in selecting the sample. Those are purposive sampling and convenience sampling. The subject consist to two groups, they were the nursing students of Stikes Mega Buana Palopo and graduate students who work in Hospital. The result of this research showed that (1) learning needs consist of language skills and learning preferences. In language skills, all the language skills are used at the rate of often in the classroom. In learning preferences of learning English with others, study in pairs is preferred than study alone, and study in small group is more preferred than study in big group while learning preferences in terms of learning by using teaching technique, study by listening and pronouncing, and by using games and role play are mostly preferred by the students. (2) Language needs consist of the use of English in workplace. regarding to use English in workplace, the graduates students hardly ever speak English in hospital. In language function, based on the graduates’ perspective about language function, all the categories fall into important level that used in hospital. (3) The syllabus design was based on the students’ need where it includes, topic, language function, teaching strategies, and language focus. Key Words: Need analysis, Syllabus, Teaching Materials, Learning Needs, Learning Style, Language Function, Teaching Strategies, and Language focus.